Uji Daya Koksidiostat Ekstrak Temulawak (Curcuma xanthorrhiza) Asal Pulau Timor pada Ayam Buras - Kurniawan, Oktav F. W.; Laut, Meity M.; Winarso, Aji (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
The development of livestock business in Indonesia has very profitable business prospects because the demand for animal products continues to grow. One of the livestock sub-sectors that are most in demand is poultry farming, especially free-range chicken. However, the development of poultry farming does not escape the obstacles faced by farmers, namely diseases, coccidiosis is one of them, which is a gastrointestinal protozoan infection caused by Eimeria spp. Coccidiosis management currently uses a coccidiostat, one of which is sulfaquinoxalin. However, sulfaquinoxalin has the disadvantage that it can cause a decrease in eggshell thickness and a decrease in feed consumption. The aim of this research is to find alternatives for the prevention and treatment of Eimeria tenella infection. This study used extracts of temulawak (Curcuma xanthorrhiza) from Timor Island. This study aims to know whether temulawak (Curcuma xanthorrhiza) extract from Timor Island is effective in treating coccidiosis and at what concentration is the most effective. The research methods included the manufacture of temulawak extract, experimental infection, collection of faecal samples, effectiveness testing and macroscopic observation of the cecum from chickens and calculating the score of the cecum lesions. This study used 3 treatment groups with 1 control. The treatment group used graded doses of temulawak (Curcuma xanthorrhiza) extract namely 0.2%, 0.4% and 0.6%, while the positive control used Coxy (©Medion) at a dose of 5 grams per liter of drinking water. The results showed that the temulawak extract (Curcuma xanthorrhiza) from the island of Timor was effective in inhibiting the growth of Eimeria tenella in vivo, with the most effective concentration of 0.2%.